Secrecy, information shocks, and corporate investment: Evidence from European Union countries - Mohamad Mazboudi; Iftekhar Hasan (Bank of Finland, 2017)
This study examines how national culture affects corporate investment. We argue that national culture affects corporate investment efficiency through the level of secrecy that national culture exhibits. Using a sample of firms from eight culturally-diverse European Union countries, we find that the level of secrecy that national culture exhibits is negatively related to corporate investment efficiency after controlling for a number of firm- and country-level factors. We also find that the negative relation between national culture and corporate investment efficiency is mitigated by an exogenous shock to the information asymmetry problem between managers and investors. Our study highlights the importance of the cultural value of secrecy/transparency as a determinant of investment efficiency at the firm-level.
URN:NBN:fi:bof-201708091483
Keywords: D82; G31; M41; 330